Cancer Radiotherapy: Enhanced Radiosensitization by Gold Nanoparticles with Acid‐Triggered Aggregation in Cancer Radiotherapy (Adv. Sci. 8/2019). Issue 8 (17th April 2019) - Zhang, Yumin; Huang, Fan; Ren, Chunhua; Liu, Jinjian; Yang, Lijun; Chen, Shizhu; Chang, Jinglin; Yang, Cuihong; Wang, Weiwei; Zhang, Chuangnian; Liu, Qiang; Liang, Xing‐Jie; et al.
Abstract : In article number1801806, Xing‐Jie Liang, Jianfeng Liu, and co‐workers develop a gold nanoparticles (GNPs) system with acid‐triggered aggregation as a radiosensitizer. With a sensitizer enhancement ratio (SER) value of 1.730 (vs. single GNPs of 1.16), this GNPs system improves sensitivity of MCF‐7 cells and MCF‐7 tumor xenograft to ionizing radiation. This work provides a strategy for fabricating radiosensitizer by in situ acid‐triggered nano‐aggregates formation.